2012
DOI: 10.3329/bjo.v18i1.10411
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology and allergen types in patients presenting with allergic rhinitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This is similar to findings by Ajiya, et al, Azam et al 4,19 irrespective of the varying prevalence across the worldwide populations and societies it have shown that the strongest risk factor for the development of allergic symptoms has been a strong family history of allergic disease. 4 The most common triggering factor of allergic rhinitis is dust particle (50.55%) which is concomitant with other observation done by Ajiya et al, Nepali, et al 4,20 The majority of patients in this study presented with complaints of running nose 96.66% which is consistent with other study done by Azam et al 19 However, the symptom with most severity was nasal itching (n= 155) followed by nasal obstruction (n=144) & sneezing (n= 122). These findings differs from other reported findings in Nijeria, India, Brazil, Nepal.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is similar to findings by Ajiya, et al, Azam et al 4,19 irrespective of the varying prevalence across the worldwide populations and societies it have shown that the strongest risk factor for the development of allergic symptoms has been a strong family history of allergic disease. 4 The most common triggering factor of allergic rhinitis is dust particle (50.55%) which is concomitant with other observation done by Ajiya et al, Nepali, et al 4,20 The majority of patients in this study presented with complaints of running nose 96.66% which is consistent with other study done by Azam et al 19 However, the symptom with most severity was nasal itching (n= 155) followed by nasal obstruction (n=144) & sneezing (n= 122). These findings differs from other reported findings in Nijeria, India, Brazil, Nepal.…”
Section: Discussionsupporting
confidence: 57%
“…These findings differs from other reported findings in Nijeria, India, Brazil, Nepal. 4,12,16,20 Studies on antihistamines are usually conducted in countries where the presence of seasonal rhinitis is quite significant. The TNSS is a widely accepted and reliable parameter to assess the efficacy of a drug in the treatment of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study gives idea of etiology and some major allergen but not about subgroup of allergen. 9 Another article identified subgroup of allergens, but range of allergens selected was very small and many locally available allergens were not included. 10 We hypothesise that pattern of distribution of allergic diseases vary across the country due to variation in climate and locally available allergens.…”
Section: Original Research Articlementioning
confidence: 99%
“…OR arising from workers inhaling colophony employed in the electronic industry is more common among female workers (24%) than males (9%). [25] Healthcare workers are at risk of OR due to possible exposure to different allergens, including formaldehyde, glutaraldehyde, drugs, natural rubber latex (gloves), while working in a hospital environment. A dentist developed OR from inhaling Nobetec, which is a temporary dental filling material that contains colophony.…”
Section: Risk Factors and Causes Of Occupational Rhinitismentioning
confidence: 99%